HFE p.C282Y heterozygosity is associated with earlier disease onset in Friedreich ataxia. Issue 7 (3rd January 2014) - Delatycki, Martin B.; Tai, Geneieve; Corben, Louise; Yiu, Eppie M.; Evans‐Galea, Marguerite V.; Stephenson, Sarah E.M.; Gurrin, Lyle; Allen, Katrina J.; Lynch, David; Lockhart, Paul J.
ABSTRACT Background Friedreich ataxia (FRDA) generally results from reduced frataxin, a mitochondrial protein involved in iron metabolism. We assessed whether HFE p.C282Y and/or p.H63D heterozygosity modifies age at disease onset or disease severity in individuals with FRDA. Methods One hundred seventy individuals with FRDA were assessed for the association of HFE p.C282Y and p.H63D with (1) age at disease onset and (2) Friedreich Ataxia Rating Scale (FARS) score. Results After adjusting for the smaller FXN GAA repeat size and sex, individuals with FRDA and heterozygous for p.C282Y had disease onset on average 3.72 years earlier than those homozygous for the wild‐type amino acid (P = 0.02). Neither mutation affected disease severity as measured by FARS. Conclusions It is hypothesized that the association between p.C282Y heterozygosity and an earlier age at FRDA onset relates to exacerbation of the already dysregulated iron metabolism that plays a major role in the pathogenesis of FRDA. © 2014 International Parkinson and Movement Disorder Society